Factors Predicting Nursing Student’s Competency in Evidence-Based Nursing - Poorananon, Pantip; Krirkgulthorn, Tassanee (Nursing Science Journal of Thailand, 2011)
Purpose: To determine the factors predicting nursing student’s competency in evidence-based nursing (EBN). Design: A correlational predictive design. Methods: The sample included 111 third-and the fourth-year nursing students in the second semester of academic year 2010 at Boromarajonani College of Nursing, Saraburi, Thailand. Data were collected using personal information records, the competency in evidence-based nursing questionnaire, attitude toward evidenced-based nursing questionnaire, the student’s perception of instructor’s behaviors in clinical teaching-learning situation questionnaire, and the student’s perception of environment for clinical practice questionnaire. Data were analyzed using Pearson product moment correlation coefficient and stepwise multiple regression. Main findings: The results showed that the student factors (grade obtained in research course, attitude toward EBN), instructor factor (student’s perception of instructor’s behaviors in clinical teaching-learning situation), and environment factor (student’s perception of environment in clinical practice) were positively related to the competency in EBN at the statistical significance level of .01. All variables could accounted for 39.6% of the variance explained in the competency. Conclusion and recommendations: The study results suggest that the appropriate study environment for clinical practice, and well-prepared instructors in terms of the teaching competency have significantly contributed to the development of nursing students’ competency in EBN.